The effect of cholesteryl ester transfer protein inhibition on lipids, lipoproteins, and markers of HDL function after an acute coronary syndrome: the dal-ACUTE randomized trial - Ray, Kausik K; Ditmarsch, Marc; Kallend, David; Niesor, Eric J; Suchankova, Gabriela; Upmanyu, Ruchi; Anzures-Cabrera, Judith; Lehnert, Valerie; Pauly-Evers, Meike; Holme, Ingar; Štásek, Josef; van Hessen, Maarten W J; et al. (European heart journal, 2014)
AIMS: The effects of cholesteryl ester transfer protein (CETP) inhibition on lipids, inflammation, and markers of high-density lipoprotein (HDL) function, following an acute coronary syndrome (ACS), are unknown. METHODS AND RESULTS: The dal-ACUTE study randomized 300 patients (1 : 1) to dalcetrapib 600 mg/day or placebo within 1 week of an ACS. The primary endpoint was per cent change in HDL-cholesterol (HDL-C) after 4 weeks. Secondary endpoints included apolipoprotein levels, markers of HDL function, and inflammation. Dalcetrapib treatment increased HDL-C and apolipoprotein A1 by 33.7 and 11.8%, respectively (both P < 0.001) and total cholesterol efflux by 9.5% (P = 0.003) after 4 weeks, principally via an increase in non-ATP-binding cassette transporter (ABC) A1-mediated efflux, without statistically significant changes in pre-β1-HDL levels. The increase in total efflux with dalcetrapib correlated most strongly with increases in apolipoprotein A1 and HDL-C (r = 0.46 and 0.43, respectively) rather than the increase in pre-β1-HDL (r = 0.32). Baseline and on-treatment ABCA1-mediated efflux correlated most strongly with pre-β1-HDL levels; in contrast, non-ABCA1-mediated efflux correlated better with apolipoprotein A1 and HDL-C levels. CONCLUSIONS: High-density lipoprotein raised through CETP inhibition with dalcetrapib improves cholesterol efflux, principally via a non-ABCA1-mediated pathway. While HDL-C was increased by one-third, apolipoprotein A1 and total efflux were increased only by one-tenth, supporting the concept of dissociation between improvements in HDL function and HDL-C levels, which may be of relevance to ongoing trials and the development of therapeutic interventions targeting HDL.
Keywords: Cholesterol Ester Transfer Proteins; Lipoproteins; sulfhydrylové sloučeniny; Male; biologické markery; HDL-cholesterol; apolipoproteiny; Apolipoproteins; Biomarkers; ATP Binding Cassette Transporter 1; ABCA1 protein; lipoproteiny; Cholesterol, HDL; Drug Administration Schedule; akutní koronární syndrom; transportní proteiny pro estery cholesterolu; nestabilní angina pectoris; C-reaktivní protein; mužské pohlaví; metabolismus lipidů; infarkt myokardu; dvojitá slepá metoda; Acute Coronary Syndrome; lidé; Sulfhydryl Compounds; ženské pohlaví; Angina, Unstable; Humans; anticholesteremika; Lipid Metabolism; Myocardial Infarction; Anticholesteremic Agents; rozvrh dávkování léků; C-Reactive Protein; Double-Blind Method; Female; lidé středního věku; Middle Aged